2008
DOI: 10.1016/j.bbmt.2007.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab-Induced Resolution of Refractory Cutaneous Chronic Graft-Versus-Host Disease

Abstract: A patient with extensive cutaneous chronic graft-versus-host disease (cGVHD) affecting 100% of the body surface, with painful ulcerations that involved 20% of it, was treated unsuccessfully during 9 months with steroids, cyclosporine-A (CSa), sirolimus, tacrolimus, mychophenolate mofetil (MMF), infliximab, and rituximab. Twenty-one months after the allograft the patient was started on alemtuzumab, 10 mg/day subcutaneously, for 6 consecutive days every 4 weeks. Seven months after starting the treatment, 100% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The colleagues from Houston have reported effectiveness of subcutaneous alemtuzumab in acute as well as chronic GVHD. 11,12 In conclusion, in this difficult to treat patient population, low doses of alemtuzumab applied every 2 weeks may lead to relevant GVHD responses with a more favourable benefit-risk ratio. This schedule should be evaluated in a prospective randomized trial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The colleagues from Houston have reported effectiveness of subcutaneous alemtuzumab in acute as well as chronic GVHD. 11,12 In conclusion, in this difficult to treat patient population, low doses of alemtuzumab applied every 2 weeks may lead to relevant GVHD responses with a more favourable benefit-risk ratio. This schedule should be evaluated in a prospective randomized trial.…”
Section: Discussionmentioning
confidence: 96%
“…Licensed for the treatment of fludarabine-refractory B-cell CLL, 2 alemtuzumab was also used in T-cell tumors [3][4][5] and due to its known immunosuppressive activity in autoimmune diseases 6 and for GVHD prevention. 7,8 Although alemtuzumab in the treatment of acute and chronic GVHD in small studies and case reports has already shown therapeutic responses, [9][10][11][12][13] very recently Schnitzler et al 14 reported 20 patients with severe intestinal acute GVHD treated successfully with alemtuzumab. Here, we show the efficacy of alemtuzumab for intestinal and liver grade III and IV acute GVHD in 18 steroid-refractory patients and support the idea that smaller doses may be preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we postulate that B cells can be directly stimulated in a Tindependent manner by transplants because their BCRs can be massively cross-linked on the surface of the allograft. This may explain the promising role of anti-CD20 therapy for the control of acute allograft rejection [42][43][44] and graft versus host disease [45]. Several models of immune-mediated tissue rejection include the expression of ISGs, infiltration of CTL and NK cells and activation of cytotoxic mechanisms (Figure 2).…”
Section: Opinionmentioning
confidence: 97%
“…However, the effect of alemtuzumab on the treatment of refractory chronic GVHD was reported only as a case report. A patient with extensive cutaneous chronic GVHD that was refractory to various immunosuppressive agents was treated with subcutaneous administration of alemtuzumab (10 mg/day for 6 consecutive days every 4 weeks) [44]. Ulcerative lesions caused by chronic GVHD and pain disappeared after 7 months of treatment, suggesting that alemtuzumab is a potentially effective drug for treating refractory chronic GVHD and its safety and efficacy should be evaluated in larger studies.…”
Section: Treatment Of Chronic Gvhdmentioning
confidence: 99%